Effects of twelve-week aerobic exercise on selected health-related physical fitness variables on Gonji preparatory school male students - Abdurahman Esleman; Bizuneh Yirga Geberemariam; Wondiye Aychiluhim (East African Journal of Biophysical and Computational Sciences, 2022)
The purpose of the present study was to investigate the effect of twelve-week aerobic exercise on health-related physical fitness components of grade eleven Gonjy preparatory school male students. The study employed an experimental research design. A simple random sampling method was used to select 30 sample students from the 242 total populations and classify them randomly into two equal experimental and control groups (n = 15). The Control group had participated in regular physical education one class of  40-minute per week in the school, but the experimental group participated additional three sessions per week for 60 minutes aerobic exercise training program, which comprised walking, jogging, running, rope skipping, and aerobic dance. Experimental and control groups had taken pre and post-test cardiorespiratory fitness, body composition, muscular endurance, muscular strength, and flexibility measured using cooper test, three-minute step test, using body mass index formula, siting tuck, chin up and sit & reach test respectively. The data collected from the study groups were analyzed by using Statistical Package for Social Science version 23 software and computed independent t-test and paired t-test and the level of significance was set at 0.05 levels. The results revealed in independent and paired t-test analysis of 12-week aerobic exercise training has significantly changed on cardiorespiratory fitness (p=0.001), muscular endurance (p=0.001) flexibility (independent p=0.04 paired p=0.02), and body mass index (p=0.001). But no significant change was observed on muscular strength in experimental and control groups of independent t-test (p=0.534 and p=0.41) and paired t-test (p=0.43 and p=0.33). Based on the finding, it was concluded that the 12 weeks aerobic exercise training program for three days per week schedule has been advantageous for the improvement of students’ health-related physical fitness variables.